Smoking Status and Metabolic Syndrome in the Multi-Ethnic Study of Atherosclerosis. A cross-sectional study - Ivan Berlin; Susan Lin; Joao A. C. Lima; Alain Gerald Bertoni (Tobacco Induced Diseases, 2012)
Background Current smoking is associated with type 2 diabetes mellitus and impaired glucose tolerance but its association with the metabolic syndrome (metS), particularly with sufficiently sampled African American representation, has not been clearly established.